2012
DOI: 10.1002/etc.1807
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutants in coastal sediment off South China in relation to the importance of anthropogenic inputs

Abstract: Abstract-Surface sediments collected from the coastal region off South China were analyzed for persistent organic pollutants (POPs), including polybrominated diphenyl ethers (PBDEs), polycyclic aromatic hydrocarbons (PAHs), and organochlorine pesticides (OCPs). The concentrations of BDE-209, S 12 PBDE, S 15 PAH, S 7 PAH, and S 11 OCP were 0.22 to 26.3, 0.01 to 0.77, 13.9 to 271, 6 to 133, and 0.9 to 104 ng/g, respectively. The spatial distribution patterns of PBDEs and PAHs suggested that the eastern coastal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
1
6
0
1
Order By: Relevance
“…Chem. 32,2013in the present study were also higher than those in riverine runoff samples of the PRD (1.10 AE 0.34) [10], and urban aerosols of Guangzhou (1.03-1.16) [22], which were attributed to anthropogenic vehicular emissions. The compositional profiles of resolved n-alkanes (Fig.…”
Section: Use Of Geochemical Markers To Trace Organic Pollutionsupporting
confidence: 40%
See 2 more Smart Citations
“…Chem. 32,2013in the present study were also higher than those in riverine runoff samples of the PRD (1.10 AE 0.34) [10], and urban aerosols of Guangzhou (1.03-1.16) [22], which were attributed to anthropogenic vehicular emissions. The compositional profiles of resolved n-alkanes (Fig.…”
Section: Use Of Geochemical Markers To Trace Organic Pollutionsupporting
confidence: 40%
“…Diagenetic perylene is normally most abundant in fine, anoxic sediments. Therefore, the prevailing anaerobic conditions for the same sampling areas in the present study [22] might suggest a diagenetic source of perylene. The seaward decline of perylene abundance in both sediments [50] and suspended particulate matter [51] from the PRE to the NSCS suggested that perylene was formed in situ in river sediments and was transported to marine sediments in association with terrestrially combustion-derived PAHs [50].…”
Section: Diagenetic Perylenementioning
confidence: 58%
See 1 more Smart Citation
“…In addition, Flu/(Flu + Pyr) values were higher than 0.5, while IcdP/(IcdP + BghiP) varied between 0.2 and 0.5, suggesting that combustions of coal, grass, wood and liquid fossil fuel were the main sources of PAHs (Yunker et al, 2002a(Yunker et al, , 2002b. This inconsistent notion was also observed in Dongjiang sediment of the PRD (Zhang et al, 2011a) and continental shelf sediment off China (Liu et al, 2012a), and it indicates that simple PAHs diagnostic indices may not be able to derive definite conclusions about input sources. Nevertheless, all these methods collectively suggested that soil PAHs in the present study were mainly sourced from combustion of coal and refined petroleum.…”
Section: Source Diagnosticsmentioning
confidence: 83%
“…Data for naphthalene, a volatile compound generally with an inconsistent recovery, were not reported. We therefore presented the sum of 15 PAHs, as in previous studies (Liu et al, 2012a(Liu et al, , 2012b. For all samples with concentration below the limits of detection (LOD), a value of zero was used in the calculation (Gu et al, 2013;Liu et al, 2012aLiu et al, , 2012b.…”
Section: Data Analysesmentioning
confidence: 99%